Color characteristics of Chinese loess and its paleoclimatic significance during the last glacial–interglacial cycle. (February 2016) - Wang, Qiansuo; Song, Yougui; Zhao, Zhijun; Li, Jijun
Highlights: Color proxies can document the variations of last glacial–interglacial cycle. L * and Hm/Gt can be regarded as indicators of East Monsoon paleoclimatic variation. Color proxies can also identify cold and warm events on millennial scale. Abstract: The soil color is widely used in paleoclimate and paleoenvironment reconstructions in the Chinese Loess Plateau. To better understand the color spatial changes during the glacial–interglacial cycle, the soil color lightness ( L * ), characteristic spectra, magnetic susceptibilities and mean grain sizes of three loess–paleosol sequences were compared. Results showed that high L * and low hematite to goethite ratios (Hm/Gt) appeared in loess units, and low L * and high Hm/Gt ratios accompanied paleosol layers, indicating glacial–interglacial hydrothermal oscillation. L * in the Yulin section was higher than in the Chaona and Lihuacun sections, indicating that different precipitations have great effect on L * . Furthermore, Hm/Gt, magnetic susceptibility ( χ lf ), and mean grain size are correlated closely with L * . L * and Hm/Gt not only document climatic variations in the glacial–interglacial cycle vis - à - vis loess–paleosol sequences, but also can identify Heinrich cold events and millennial scale Dansgaard–Oeschger (D–O) warm events. It suggests that soil color responds sensitively to global climate change driven by ice volumes. L * and Hm/Gt curves exhibit higher frequencies and larger amplitudes than magnetic susceptibility ( χ lf ) curves, indicating that L * and Hm/Gt can be regarded as sensitive and reliable proxies for characterizing high-resolution climate change during the last glacial–interglacial cycle.